2018
DOI: 10.1074/jbc.ra118.003129
|View full text |Cite
|
Sign up to set email alerts
|

ER-resident protein 46 (ERp46) triggers the mannose-trimming activity of ER degradation–enhancing α-mannosidase–like protein 3 (EDEM3)

Abstract: Protein folding in the cell is regulated by several quality-control mechanisms. Correct folding of glycoproteins in the endoplasmic reticulum (ER) is tightly monitored by the recognition of glycan signals by lectins in the ER-associated degradation (ERAD) pathway. In mammals, mannose trimming from -glycans is crucial for disposal of misfolded glycoproteins. The mannosidases responsible for this process are ER mannosidase I and ER degradation-enhancing α-mannosidase-like proteins (EDEMs). However, the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…TXNDC11 was recently reported to be a disulfide reductase with a role in ERAD and to associate with EDEM2 and EDEM3 27 . Very recently, while this manuscript was in revision, it was reported that EDEM3 associates with another oxidoreductase, ERp46, which promotes its mannose-trimming activity 18 . In this case, the redox environment did not affect EDEM3 activity, and thus ERp46 did not affect EDEM3 per se, suggesting that the complex may reduce the misfolded substrate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…TXNDC11 was recently reported to be a disulfide reductase with a role in ERAD and to associate with EDEM2 and EDEM3 27 . Very recently, while this manuscript was in revision, it was reported that EDEM3 associates with another oxidoreductase, ERp46, which promotes its mannose-trimming activity 18 . In this case, the redox environment did not affect EDEM3 activity, and thus ERp46 did not affect EDEM3 per se, suggesting that the complex may reduce the misfolded substrate.…”
Section: Discussionmentioning
confidence: 95%
“…Although it was shown that overexpression or depletion of the EDEMs affects the trimming of mannose residues (EDEM1 11 , 15 , 16 , EDEM2 12 , EDEM3 17 ), mannosidase activity has not yet been established in vitro for EDEM1 and EDEM2. Mannosidase activity has already been determined in vitro for ERManI and mannosidase IA and very recently for EDEM3 18 . It has also been reported for the Saccharomyces cerevisiae EDEM homolog Htm1, which functions in a complex with protein disulfide isomerase (PDI) 19 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, ERdj3 was recently implicated in the degradation of the Z variant (37). Additionally, the EDEM3 MLD was recently discovered to form a disulfide bond with the oxidoreductase ERp46, which promoted the catalytic activity of EDEM3 (38). Whether these oxidoreductases or others are involved in the redox-sensitive substrate-binding properties of EDEM1 remains to be determined.…”
Section: Edem1 Redox-sensitive Binding and Catalytic Activitymentioning
confidence: 99%
“…A recent study revealed that EDEM3 can associate stably with ERp46 (also called TXNDC5), another ER-resident oxidoreductase. This association was required for the mannosidase activity on misfolded substrate glycoproteins [ 67 ]. In vitro degradation of misfolded TCRα was reconstituted only when ERp46 had established a covalent interaction with EDEM3.…”
Section: Involvement Of Oxidoreductases In Mannose Trimming Of Unfmentioning
confidence: 99%
“…This interaction, which depended on the redox activity of ERp46, involved formation of a disulfide bond between the cysteine residues of the ERp46 catalytic sites and the EDEM3 α-mannosidase domain. ERp46 does not directly change EDEM3 activity, and probably plays a role similar to that of TXNDC11 and PDI for EDEM1 and 2 activity, acting on the glycoprotein substrate [ 67 ]. Another study found a thiol-dependent substrate association of EDEM1 with the misfolded α1-antitrypsin variant Null Hong Kong (NHK), through a single Cys residue of the substrate, but this did not involve EDEM1 thiols.…”
Section: Involvement Of Oxidoreductases In Mannose Trimming Of Unfmentioning
confidence: 99%